PENGARUH JOB INSECURITY DAN WORK-LIFE BALANCE TERHADAP STRES KERJA PADA PERAWAT RUMAH SAKIT SWASTA DI KECAMATAN BUMIAYU - Anggit Rima Danti; Dyah Astorini Wulandari; Imam Faisal Hamzah; Gisella Arnis Grafiyana (CV. Denasya Smart Publisher, 2026)
High job demands, long working hours, and employment uncertainty place nursesparticularly those working in private hospitalsat increased risk of work-related stress. These conditions are further influenced by imbalances between professional responsibilities and personal life. This study aimed to examine the effects of job insecurity and work-life balance on work stress among nurses working in private hospitals in Bumiayu District.This study employed a quantitative method with a correlational approach. The sample consisted of 184 male and female nurses aged 2035 years, selected using simple random sampling. Data were collected using standardized scales measuring work stress, job insecurity, and work-life balance. Data analysis was conducted using SPSS version 26.0. Hypothesis testing indicated that job insecurity had a positive and significant effect on work stress (F = 173.152; p 0.05). Work-life balance had a negative and significant effect on work stress (F = 173.152; p 0.05). Simultaneously, job insecurity and work-life balance had a significant effect on work stress (F = 124.454; p 0.05).